Prices and clinical benefit of cancer drugs in the USA and Europe: a cost–benefit analysis. Issue 5 (May 2020) - Vokinger, Kerstin N; Hwang, Thomas J; Grischott, Thomas; Reichert, Sophie; Tibau, Ariadna; Rosemann, Thomas; Kesselheim, Aaron S
Summary: Background: Increasing cancer drug prices are a challenge for patients and health systems in the USA and Europe. By contrast with the USA, national authorities in European countries often directly negotiate drug prices with manufacturers. The American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO) developed frameworks to evaluate the clinical value of cancer therapies: the ASCO-Value Framework (ASCO-VF) and the ESMO-Magnitude of Clinical Benefit Scale (ESMO-MCBS). We aimed to assess the association between the clinical benefit of approved cancer drugs based on these frameworks and their drug prices in the USA and four European countries (England, Switzerland, Germany, and France). Methods: For this cost–benefit analysis, we identified all new drugs with initial indications for adult cancers that were approved by the US Food and Drug Administration between Jan 1, 2009, and Dec 31, 2017, and by the European Medicines Agency up until Sept 1, 2019. For drugs indicated for solid tumours, we assessed clinical benefit using ASCO-VF and ESMO-MCBS. We compared monthly drug treatment costs between benefit levels using hierarchical linear regression models, and calculated Spearman's correlation coefficients between costs and benefit levels for individual countries. Findings: Our cohort included 65 drugs: 47 (72%) drugs were approved for solid tumours and 18 (28%) were approved for haematological malignancies. The monthly drug treatment costs in the USA were a median of 2·31 times (IQR 1·79–3·17) as high as in the assessed European countries. There were no significant associations between monthly treatment costs for solid tumours and clinical benefit in all assessed countries, using the ESMO-MCBS (p=0·16 for the USA, p=0·98 for England, p=0·54 for Switzerland, p=0·52 for Germany, and p=0·40 for France), and for all assessed countries except France using ASCO-VF (p=0·56 for the USA, p=0·47 for England, p=0·26 for Switzerland, p=0·23 for Germany, and p=0·037 for France). Interpretation: Cancer drugs with low or uncertain clinical benefit might be prioritised for price negotiations. Value frameworks could help identify therapies providing high clinical benefit that should be made rapidly available across countries. Funding: Swiss Cancer Research Foundation (Krebsforschung Schweiz).